Emerging presence of Actinomyces in perianal and pilonidal infection. Issue 8 (17th August 2022) - Tan, Chih Y; Javed, Muhammad A; Artioukh, Dmitri Y
Abstract: Actinomyces is a rare aetiology of infections affecting the perianal region and natal cleft. Recognition of this microorganism is essential to deliver targeted antimicrobial therapy following surgical intervention. We present a series of 15 pilonidal and perianal infections associated with this microorganism. Actinomyces turicensis was the only strain of Actinomyces isolated. A total of 14 out of 15 cases had concomitant microorganisms isolated from microbiology specimens. Mixed anaerobes ( n = 14) were the most common concomitant pathogens followed by Streptococcus milleri ( n = 3), Staphylococcus aureus ( n = 1), Citrobacter ( n = 1) and Coliform bacteria ( n = 1). All patients, except one who was pregnant at time of diagnosis, underwent surgical drainage with or without further oral antibiotic therapy. Coloproctologists need to consider Actinomyces as a clinically significant pathogen in the context of perianal and pilonidal infections.